Personal Application - the Basis for Dismissal of a Public Servant - Loria, Khatuna (Journal of Law, 2023)
The dismissal of a public servant based on a personal application is a discretional (optional) ground for dismissal which is related to the right of a person. It is a refusal of service but on the other hand, it obligates a public institution to obey a choice of a person. The article reviews the issues followed by the dismissal of a public servant on this basis. It also highlights the freedom of an officer's will, the purpose of protecting the interest of public service, and judicial practice, and the restriction of the right to dismiss the personal application.